2018
DOI: 10.2169/internalmedicine.9300-17
|View full text |Cite
|
Sign up to set email alerts
|

A Favorable Response to Levetiracetam in a Patient with Metastatic Adenoid Cystic Carcinoma

Abstract: Adenoid cystic carcinoma (ACC) is a rare cancer, and there are no standard-of-care treatments for patients with metastatic ACC. We herein report a patient with lung metastasis of ACC who achieved a favorable response to levetiracetam. A 52-year-old Japanese man was admitted to our hospital because of multiple lung metastases of ACC. We performed first-line chemotherapy with cisplatin plus gemcitabine, and subsequently oral S-1 as second-line chemotherapy, which resulted in disease progression. The patient deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Levetiracetam has never been tested in prostate cancer cells before our study, whereas it has already showed anti-proliferative capacity against glioma cells in vitro ( 31 ). Albeit clinical testing of levetiracetam in patients with glioblastoma did not associate with improved progression-free survival and/or overall survival ( 32 ), a case report documented regression of lung metastatic lesions in a man with adenoid cystic carcinoma, in which levetiracetam was administered with the sole intent to relief epilepsy, and after the failure of several lines of therapy against the tumor ( 33 ). Here, we show that levetiracetam has some efficacy against both adenocarcinoma and NEPC, in vivo , in subcutaneous and spontaneous murine models.…”
Section: Discussionmentioning
confidence: 99%
“…Levetiracetam has never been tested in prostate cancer cells before our study, whereas it has already showed anti-proliferative capacity against glioma cells in vitro ( 31 ). Albeit clinical testing of levetiracetam in patients with glioblastoma did not associate with improved progression-free survival and/or overall survival ( 32 ), a case report documented regression of lung metastatic lesions in a man with adenoid cystic carcinoma, in which levetiracetam was administered with the sole intent to relief epilepsy, and after the failure of several lines of therapy against the tumor ( 33 ). Here, we show that levetiracetam has some efficacy against both adenocarcinoma and NEPC, in vivo , in subcutaneous and spontaneous murine models.…”
Section: Discussionmentioning
confidence: 99%